Novel 3D statistical shape models for segmentation of medical images - Zhao, ZheEn (2008)
This thesis presents the development of 3D Statistical Shape Models (SSMs) for automated segmentation of 3D medical images. It also presents the automated methods for construction of Point Distribution Models (PDMs). The proposed algorithms are applied for the segmentation of 3D human brain Magnetic Resonance Images (MRIs).